Training Set for Automatic Conveyor Belt System - na ranong, Chaiwat; Botmatra, Chonlapat; Faichokchai, Kananon (Institute of Vocational Education Southern Region 3 Journal (KRIS Journal), 2021)
The objectives of the research were to: (1) create an automatic conveyor belt system practice set, (2) study the efficiency of an automatic conveyor belt system practice set, and (3) study the students' satisfaction on the automatic conveyor belt system practice set and their satisfaction on the worksheet. The conveyor system could control the operation with sensors for inspecting and sorting metal, non-metallic objects, work piece color and assembly. The first step was on programming the microcontroller, then the structure and type of belts were designed to create simulation models for testing the operation of the system. Once the belt model design has been completed, the size of the motor to drive the belt was calculated and the circuitry to drive the motor was designed. When the belt part was completed, the data of the results on using the automatic conveyor system practice set was collected. The students were asked to follow the worksheet during and after the class training. The satisfaction questionnaires were completed. This research could investigate the operation of the production belt system and check the quality of the work piece. In conclusion, the research findings revealed an efficiency value of E1 worksheets during the study with the automatic conveyor belt system practice set of 70.49 while the efficiency value of E2 worksheets after studying with the automatic conveyor belt practice set was 81.86.